2010
DOI: 10.7124/bc.000151
|View full text |Cite
|
Sign up to set email alerts
|

New technique of identifying the hierarchy of dynamic domains in proteins using a method of molecular dynamics simulations

Abstract: Aim. Despite a large number of existing domain identification techniques there is no universally accepted method, which identifies the hierarchy of dynamic domains using the data of molecular dynamics (MD) simulations. The goal of this work is to develop such technique. Methods. The dynamic domains are identified by eliminating systematic motions from MD trajectories recursively in a model-free manner. Results. The technique called the Hierarchical Domain-Wise Alignment (HDWA) to identify hierarchically organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…An exhaustive comparison of structural domains, determined by various algorithmic methods, with manual domain assignments showed that especially the number of assigned domains differs, while the domain boundaries usually agree well. Accordingly, hierarchical levels of domain partitioning, which should be interpreted in a context-dependent manner, were proposed by several authors. ,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An exhaustive comparison of structural domains, determined by various algorithmic methods, with manual domain assignments showed that especially the number of assigned domains differs, while the domain boundaries usually agree well. Accordingly, hierarchical levels of domain partitioning, which should be interpreted in a context-dependent manner, were proposed by several authors. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Besides, dynamic domains can help to identify perturbation-sensitive sites of proteins, where addition or removal of a few interactions lead to large changes of protein dynamics. Several methods identify rigid domains based on coordinates given by two conformations, representing the open and the closed state of a protein , or based on snapshots from Molecular Dynamics simulations , and NMR ensembles . Another common approach is to use principal components, calculated from a structural ensemble, or normal modes.…”
Section: Introductionmentioning
confidence: 99%
“…Pteros is used to implement the Hierarchical Clustering of Correlation Patterns [14,15] and the Hierarchical Domain-Wise Alignment [16][17][18] algorithms, which are novel techniques of dynamic domains identification in proteins. The method of Hierarchical Rotations (HIEROT), which allows simulating slow large-scale motions of dynamic domains [19,20] is also implemented using Pteros.…”
Section: Applications Of Pterosmentioning
confidence: 99%